Legislation and policy for involuntary mental healthcare across countries in the FOSTREN network: rationale, development of mapping survey and protocol - Aluh, Deborah Oyine; Lantta, Tella; Lourenço, Tânia; Birkeland, Søren Fryd; Castelpietra, Giulio; Dedovic, Jovo; Caldas-de-Almeida, José Miguel; Rugkåsa, Jorun (CAMBRIDGE UNIV PRESS, 2026)
Background
Several countries are currently revising or have already revised their mental health laws to align with the global movement to reduce the use of coercive care. No government has yet fully implemented the recommendation of the United Nations Convention on the Rights of Persons with Disabilities (UNCRPD) to eliminate the use of coercion in mental healthcare. Consequently, the international field of mental health law and policy is in a degree of flux.
Aims
To describe the rationale, development and protocol for a project that will map and examine how mental health laws, policies and service capacity across European countries relate to the use of coercive measures, including involuntary admissions and treatment, restraints and seclusion. This will help to better understand the current situation and explore future directions of policies regarding coercive care.
Method
The project is being carried out under the purview of the European Cooperation in Science and Technology (COST) action network, entitled FOSTREN (Fostering and Strengthening Approaches to Reducing Coercion in European Mental Health Services). A multidisciplinary group of experts developed a comprehensive survey assessing mental health laws, policies and service frameworks, based on World Health Organization and UNCRPD recommendations. The survey was piloted in three countries, revised and disseminated to 30 FOSTREN country representatives. The survey will provide data for three strands of work on legislation, policies and service-level context. A comprehensive evaluation will be conducted, drawing on findings from all work packages.
Conclusions
The project could inform the development of strategies, interventions and legislation to address gaps and promote compliance with international standards.